Distinctive Acellular Lipid Emboli in Hemoglobin SC Disease following Bone Marrow Infarction with Parvovirus Infection - Danielle M. Graff; Erin Owen; Robert Bendon; Salvatore Bertolone; Ashok Raj (Case Reports in Hematology)
An adolescent with mild hemoglobin SC disease presented with pelvic pain with subsequent respiratory and neurologic deterioration, which led to ultimately death. The autopsy demonstrated acellular fat emboli particularly in the lung and brain. There was marrow necrosis in the lumbar spine with aggregated sickle cells and positive parvovirus immunostaining. The brain lesion both grossly and microscopically presented a distinct pathology of acellular fat emboli that led to the correct diagnosis of this increasingly recognized association of sickle hemoglobinopathies with fat embolism syndrome (FES). A clinical diagnosis of FES is difficult to confirm in many patients with sickle hemoglobinopathy presenting with pain crisis because of concurrent illness. However, this case report highlights the need for a thorough knowledge of the signs and symptoms of the syndrome and a high index of suspicion for the diagnosis to be made premortem.